Educação em ciências e matemática no ensino médio inovador : uma análise sobre integração curricular - Cruz, Ana Cristina da (2016)
This research focuses on the Curricular Integration in Natural Sciences and Mathematics in the context of a Pro-EMI innovative high school. The goal is to understand conceptions related to curricular integration in two schools in the state of Mato Grosso identifying propositions and practices of curricular integration in the areas of Natural Sciences and Mathematics. The referential that guide the research and analysis are based in the theoretical contributions of authors who deal with educational policies (Ball, 1987, 1992, 2001, 2002a, 2002b, 2006), innovation (MESSINA, 2001 and CARBONELL, 2002), curriculum and curricular integration (BEANE, 1997; FERREIRA et al 2014 FERREIRA & JAEHN, 2012; LOPES, 2001, 2008; LOPES and MACEDO, 2002 and 2011; MACEDO, 2006; SACRISTÁN, 2000; SANTOMÉ, 1998) and high school (FRIGOTTO, 2003; and FRIGOTTO CIAVATTA, 2003). The research methodology, the qualitative type, was guided by a desire to seek answers to the following problem: How is conceived and developed curricular integration in the area of natural sciences and Mathematics in the context of Innovative High School in two schools in the state of MT? Eight teachers made part of investigation in the areas of Natural Sciences and Mathematics and two articulators of ProEMI actions. Data were collected through official documents (international, national, state and scholar), observations and semi-structured interviews. The analyzes indicate that most teachers do not understand the objectives and the proposal of curriculum redesign at ProEMI; however, we can see efforts in order to favor the learning of students. The curricular integration tends to be associated with interdisciplinarity and development of curricular projects with more emphasis on diverse part of the curriculum. Although official curricular documents (PCNEM, OCNEM, DCNEM), giving emphasis to the speech of the integrated curriculum, from the areas of knowledge, in practice this purpose proved to be fragile. The analyzes also indicate that the presupposition of curriculum organization through the integrating axis "work, science, culture and technology" tends to be obliterated. One of the factors identified as limit of curricular integration is the initial and continuing teacher training. In summary, the analyzes confirm the thesis that the curricular policies are not implemented by virtue of official texts that seek to promote innovation and change in pedagogical work. It happens because the curriculum is space of tensions, disputes, reterritorializations and hybridism due to the performance of teachers and the conditions of educational institutions.